Influence of Sexually Transmitted Infections in Pregnant Adolescents on Preterm Birth and Chorioamnionitis - Esther Fuchs; Maggie Dwiggins; Erica Lokken; Jennifer A. Unger; Linda O. Eckert (Hindawi Limited, 2020)
Background. Adolescents have an increased risk of preterm birth (PTB) and sexually transmitted infections (STIs). We examined the prevalence and impact of STIs (gonorrhea, chlamydia, and trichomonas) on PTB and chorioamnionitis in pregnant adolescents. Methods. This retrospective cohort study utilized the first pregnancy delivered at an urban hospital among patients≤19 years old over a 5-year period. Poisson regression with robust standard errors was used to estimate prevalence ratios (PR) and 95% confidence intervals (CI) of the association between STIs and PTB (<37 weeks) and chorioamnionitis identified by clinical or placental pathology criteria. Results. 739 deliveries were included. 18.8% (n=139) of births were preterm. The overall prevalence of STIs during pregnancy was 16.5% (Chlamydia trachomatis: 13.1%, n=97; Trichomonas vaginalis: 3.7%, n=27; and Neisseria gonorrheae: 3.1%, n=23). Detection of C. trachomatis, T. vaginalis, or N. gonorrheae was not associated with increased PTB. While infection with N. gonorrheae and C. trachomatis did not increase the likelihood of any chorioamnionitis, infection with T. vaginalis significantly increased the likelihood of any chorioamnionitis diagnosis (aPR 2.19, 95% CI 1.26-3.83). Conclusion. In this adolescent population with a high rate of PTB, in whom most received appropriate STI treatment, we did not find an association between STI during pregnancy and an increased rate of PTB. However, an infection with T. vaginalis was associated with an increased likelihood of chorioamnionitis. Early detection of STIs may prevent adverse pregnancy outcomes. Continued vigilance in STI screening during pregnancy, including consideration of universal Trichomonas vaginalis screening, is merited in this high-risk population.